2001
DOI: 10.1021/ja010453j
|View full text |Cite
|
Sign up to set email alerts
|

Total Structure Determination of Apratoxin A, a Potent Novel Cytotoxin from the Marine Cyanobacterium Lyngbya majuscula

Abstract: Apratoxin A (1), a potent cytotoxin with a novel skeleton, has been isolated from the marine cyanobacterium Lyngbya majuscula Harvey ex Gomont. This cyclodepsipeptide of mixed peptide-polyketide biogenesis bears a thiazoline ring flanked by polyketide portions, one of which possesses an unusual methylation pattern. Its gross structure has been elucidated by spectral analysis, including various 2D NMR techniques. The absolute configurations of the amino acid-derived units were determined by chiral HPLC analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
215
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 345 publications
(228 citation statements)
references
References 37 publications
9
215
0
4
Order By: Relevance
“…They concluded that apratoxin A exhibits potent cytotoxicity for cancer cells, with IC 50 values of 0.52 nM against KB and 0.36 nM against LoVo cancer cells 4,5) (Fig. 1).…”
Section: Apratoxin Amentioning
confidence: 99%
“…They concluded that apratoxin A exhibits potent cytotoxicity for cancer cells, with IC 50 values of 0.52 nM against KB and 0.36 nM against LoVo cancer cells 4,5) (Fig. 1).…”
Section: Apratoxin Amentioning
confidence: 99%
“…Using a previously established molecular modeling protocol suitable for cyclodepsipeptides, 19 10 randomly drawn structures of 1 were subjected to distance geometry, 20 followed by simulated annealing and finally restrained molecular dynamics simulation for 1 ns. The modeled structures could be divided into two distinct conformational families.…”
mentioning
confidence: 99%
“…通过比 对分析, apratoxin A 的构效关系(图 4)也可从中窥得一 斑 [18,19] . [3] 0.36 [3] 1.4 [20] 10 [20] /2.2 [7] /190 [9] 10 [20] 5.97 [21] /1.21 [18] 2.5 [19] 70 21.3 [22] 10.8 [22] 71 1.0 [22] 0.73 [22] 72 2.6 [23] 73 21 [20] 72 [20] 59 [20] 184 [21] 74 4.92 [21] 2 [18] 75 14 [18] 76 3.4 [19] 77 89.9 [19] 78 37.6 [22] 85.1 [22] 41 [20] 121 [20] 160 [20] 79 9.7 [7] /380 [9] 80 920 [7] 81 >10000 [7] 82 >10000 [7] 83 1.14 [21] 84 258 [21] 85 1.58 [21] 86 373 [21] 87 4.15 [21] 88 1700 [21] 89 28000 [9] 90 450 [9] 91 2100 [9] 92 1700 [9] 93 80 [9] 94 350 [9] 95 30 [9] 3...…”
Section: Methodsmentioning
confidence: 99%